Preparation method and application of fluorescent composite film

The high quantum yield L-CQDs were prepared by adding specific aminobenzoic acid to alkali lignin and reacting with sulfuric acid, and mixed with bagasse-based CNF to build a hydrogen bond network, which solved the aggregation problem of L-CQDs in the solid state, and achieved the realization of the realization of L-CQDs. It has high efficiency long-wavelength luminescence and good luminescence stability, and is suitable for LED luminescence layer materials.

CN119220248APending Publication Date: 2024-12-31GUANGXI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411344272.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The carbon quantum dot fluorescence quantum yields prepared by polymer lignin are low, making it difficult to achieve long-wavelength luminescence, and the aggregation-induced quenching effect in the solid state limits its application in LED devices.

Method used

The lignin-based carbon quantum dots (L-CQDs) with high quantum yields are prepared by adding 3,4-diaminobenzoic acid or 3,5-diaminobenzoic acid to alkali lignin and reacting with deionized water and sulfuric acid. ), and then mixed with bagasse-based carbon nanofibers (CNF), fluorescent composite films were prepared by sonication and casting method to construct L-CQDs/CNF hydrogen bond network to inhibit quenching caused by solid-state aggregation.

Benefits of technology

L-CQDs with high quantum yield and long wavelength emission were obtained. The prepared fluorescent composite film has good luminescence stability and is suitable for LED luminescence layer, realizing a green and degradable LED luminescence layer material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119220248A_ABST
    Figure CN119220248A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of composite films, in particular to a preparation method and application of a fluorescent composite film, and the preparation method comprises the following steps: (1) preparation of L-CQDs, (2) preparation of CNF and (3) preparation of the fluorescent composite film. The fluorescent composite film obtained through the method has the potential of being used as an LED base material in the aspects of optical performance, mechanical performance, thermal stability and the like, and can be used as an LED light-emitting layer for assembling and preparing a light-emitting diode.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The invention belongs to the technical field of composite films, and in particular relates to a preparation method of a fluorescent composite film and application thereof. [Background technology]

[0002] Light-emitting diodes (LEDs) are expected to become the next generation of ideal lighting and display devices due to their high energy efficiency, long service life, fast response speed, high reliability, small size, and simple structure. Lignin-based carbon quantum dots (L-CQDs) are expected to become ideal fluorescent materials for LEDs due to their unique luminescence properties, high stability, and low toxicity.

[0003] However, the fluorescence quantum yield of L-CQDs prepared from polymer lignin is generally low, and it is difficult to achieve long-wavelength luminescence, which hinders the preparation of high-efficiency, multi-color LEDs. In addition, the aggregation-induced quenching effect (ACQ) of carbon quantum dots (CQDs) in the solid state limits their application in LED devices. [Summary of the invention]

[0004] In view of the above, it is necessary to provide a method for preparing a fluorescent composite film and its application. The fluorescent composite film obtained by the method of the present application has the potential to be used as an LED substrate in terms of optical properties, mechanical properties and thermal stability, and can be assembled as an LED light-emitting layer to prepare light-emitting diodes.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is:

[0006] A method for preparing a fluorescent composite film, the method comprising the following steps:

[0007] (1) Preparation of L-CQDs: 3,4-diaminobenzoic acid or 3,5-diaminobenzoic acid is added to alkaline lignin, followed by deionized water and sulfuric acid. After mixing, the mixture is transferred to a reactor, and the reactor is placed in an electric heating blast drying oven. The reaction is carried out at 180-220° C. for 10-14 h. After the reaction is completed, the reaction is naturally cooled to room temperature. The obtained product is then filtered, and the supernatant is dialyzed in ultrapure water for 2-4 days using a dialysis bag. The dialyzed solution is evaporated and freeze-dried to obtain L-CQDs solid powder for later use;

[0008] (2) Preparation of CNF: Mix hydrogen peroxide and acetic acid in a beaker to obtain a peroxy-acetic acid solution, place bagasse in a conical flask, add HPAA solution, then add sulfuric acid solution, and adjust the solid-liquid ratio (W / V) to 1:8-12 (g:mL). After sufficient mixing, place in a constant temperature water bath and pre-treat at 70-90°C for 1-3h. After the water bath ends, cool to room temperature, rinse the solid residue with deionized water to neutrality after solid-liquid separation, and dry the washed solid to obtain bagasse slurry; add deionized water to the obtained bagasse slurry to adjust the concentration to 1-2wt%, soak for 22-25h, and then decompose the soaked slurry for 10-20min to prepare a 1-3wt% fiber suspension. Then, grind the fiber suspension to obtain a CNF sample;

[0009] (3) Preparation of fluorescent composite film: L-CQDs powder was added to deionized water to form a transparent and clear L-CQDs solution, the L-CQDs solution was mixed with CNF, and stirred at room temperature to be evenly dispersed, and then the resulting mixture solution was ultrasonically treated. The L-CQDs / CNF solution obtained after ultrasonic treatment was added to a mold for casting and precipitated at room temperature to finally obtain a fluorescent composite film.

[0010] In the present invention, further, in the step (1), the mass ratio of alkali lignin to 3,4-diaminobenzoic acid or 3,5-diaminobenzoic acid is 1:1, the solid-liquid ratio of the added deionized water to the alkali lignin is 1g:190mL; the solid-liquid ratio of the added sulfuric acid to the alkali lignin is 1g:10mL.

[0011] In the present invention, further, the product is filtered in step (1) by using a 0.22 μm nylon microporous membrane, and the supernatant is dialyzed in ultrapure water using a dialysis bag for 3 days, during which the water is changed every 6 hours.

[0012] In the present invention, further, in step (2), the volume ratio of hydrogen peroxide to acetic acid is 1:1.

[0013] In the present invention, further, in the step (2) of grinding process, the method for regulating the distance between the grinding stones is as follows: when the ultrafine grinding machine is idling, the critical point where the two grinding stones initially contact is defined as the dynamic zero point. After the slurry is added, the distance between the two grinding stones is gradually adjusted from the dynamic zero point to -100 μm, and then grinding is continued for 2 hours.

[0014] In the present invention, further, the solid-liquid ratio of the L-CQDs powder and deionized water in step (3) is 1 mg:1 mL, and the mass ratio of the L-CQDs powder to CNF is 1:60.

[0015] The invention also provides application of the fluorescent composite film in preparing light-emitting diodes.

[0016] The present invention also provides a method for preparing a light-emitting diode, wherein the light-emitting diode is obtained by treating an LED lamp bead with the fluorescent composite film described in any one of claims 1 to 6, and the specific method is as follows: a layer of ultraviolet light-curing glue is applied to the edge of a 1W ultraviolet LED lamp bead, with a powder-to-glue mass ratio of 1:1, and then, the fluorescent composite film is taken to cover the surface of the lamp bead. At the same time, in order to realize LED film encapsulation and the application of LED in a humid environment, a layer of ultraviolet light-curing glue is applied to the surface of the fluorescent composite film, and a 365nm ultraviolet lamp is used for irradiation for 3 minutes for light curing, so that the treated LED device (i.e., the light-emitting diode) can be obtained.

[0017] The present invention has the following beneficial effects:

[0018] 1. The present invention regulates the content of lignin in bagasse-based LCNF by HPAA pretreatment assisted by mechanical grinding, obtains a LCNF film with high haze and good water barrier, and at the same time, prepares lignin-based L-CQDs with high quantum yield and long wavelength emission.

[0019] 2. In order to obtain a green and degradable LED light-emitting layer, the present invention constructs a L-CQDs / LCNF hydrogen bond network through the hydrogen bond interaction between LCNF and L-CQDs, suppresses the quenching phenomenon caused by the solid-state aggregation of L-CQDs, and realizes the solid-state luminescence characteristics of L-CQDs. The fluorescent composite film obtained by the method of the present invention and the prepared LED have good luminescence stability and can be used in the optoelectronic field.

Brief Description of the Drawings

[0020] Figure 1 The chemical components of bagasse pulp after pretreatment with HPAA at different concentrations;

[0021] Figure 2 This is the optical performance analysis diagram of CNF film, where: Figure 2 (a) is the CNF film transmittance (200-800nm), Figure 2 (b) is the haze of the CNF film sample, Figure 2 (c) is the transparency and haze value of the CNF film sample at 600nm, Figure 2 (d) is a photograph of the film;

[0022] Figure 3 Schematic diagram of water contact angle of different CNF films;

[0023] Figure 4 is the luminous performance of BL-CQDs / LCNF-100LED: Figure 4 (a) Electroluminescence spectrum, Figure 4 (b) Real object luminescence diagram and Figure 4 (c) CIE chromaticity coordinates;

[0024] Figure 5 This is the effect of current change on the luminous performance of BL-CQDs / LCNF-100LED: Figure 5 (a) is the EL spectrum at 20mA-120mA current, Figure 5 (b) is the color coordinates and color temperature distribution and Figure 5 (c) is the luminous efficiency at different currents. [Specific implementation method]

[0025] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and understandable, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific implementation disclosed below.

[0026] Embodiment 1:

[0027] This embodiment provides a method for preparing a fluorescent composite film, the method comprising the following steps:

[0028] (1) Preparation of L-CQDs: 0.1 g of 3,4-diaminobenzoic acid was added to 0.1 g of alkali lignin, followed by 19 mL of deionized water and 1 mL of sulfuric acid. After mixing, the mixture was transferred to a 50 mL polytetrafluoroethylene-lined stainless steel reactor. The reactor was placed in an electric heated blast drying oven and reacted at 180 °C for 10 h. After the reaction was completed, the reaction mixture was naturally cooled to room temperature. The obtained product was then filtered with a 0.22 μm nylon microporous membrane. The supernatant was dialyzed in ultrapure water with a dialysis bag (MWCO = 1000 Da) for 2 days. During this period, the water was changed every 6 h. The dialyzed solution was evaporated using a parallel concentrator to reduce some of the water content. Finally, the L-CQDs solid powder was freeze-dried for later use.

[0029] (2) Preparation of CNF: Hydrogen peroxide (30%) and acetic acid (≥99%) were mixed in a beaker at a volume ratio of 1:1 to obtain a peroxy-acetic acid solution. 10 g of sugarcane bagasse was placed in a conical flask and HPAA solution (V HPAA :V 水=100:0), then add 100mM sulfuric acid solution as a catalyst, and adjust the solid-liquid ratio to 1:8 (W / V), after fully mixing, place in a constant temperature water bath, pre-treat at 70°C for 1h, after the water bath ends, cool to room temperature, use a separatory funnel to achieve solid-liquid separation, and then use deionized water to rinse the solid residue to neutrality, transfer the washed solid to an electric hot air drying oven and dry at 40°C to obtain bagasse slurry; add deionized water to the obtained bagasse slurry to adjust the concentration to 1wt%, soak for 22h, and then disperse the soaked slurry for 10min to prepare a 1wt% fiber suspension, and then grind the fiber suspension. During the grinding process, the method for regulating the distance between the grinding stones is as follows: when the ultrafine grinding machine is idling, the critical point where the two grinding stones initially contact is defined as the dynamic zero point. After the slurry is added, the distance between the two grinding stones is gradually adjusted from the dynamic zero point to -100μm, and then ground for 2h to obtain CNF samples, which are stored in a refrigerator for standby use;

[0030] (3) Preparation of fluorescent composite film: 5 mg of L-CQDs powder was added to 5 mL of deionized water to form a transparent and clear L-CQDs solution. The L-CQDs solution was mixed with 0.3 g of CNF (absolutely dry) and mechanically stirred at room temperature for 1 h at a speed of 600 rpm to allow the L-CQDs to be evenly dispersed in the CNF solution. The resulting mixture solution was then ultrasonically treated to remove bubbles. The L-CQDs / CNF solution obtained after ultrasonic treatment was then added to a mold for casting and precipitated at room temperature to finally obtain a fluorescent composite film.

[0031] Embodiment 2:

[0032] This embodiment provides a method for preparing a fluorescent composite film, the method comprising the following steps:

[0033] (1) Preparation of L-CQDs: 0.1 g of 3,4-diaminobenzoic acid was added to 0.1 g of alkali lignin, followed by 19 mL of deionized water and 1 mL of sulfuric acid. After mixing, the mixture was transferred to a 50 mL polytetrafluoroethylene-lined stainless steel reactor. The reactor was placed in an electric heated air drying oven and reacted at 200 °C for 12 h. After the reaction, the reaction mixture was naturally cooled to room temperature. The obtained product was then filtered with a 0.22 μm nylon microporous membrane. The supernatant was dialyzed in ultrapure water using a dialysis bag (MWCO = 1000 Da) for 3 days. During this period, the water was changed every 6 h. The dialyzed solution was evaporated using a parallel concentrator to reduce some of the water content. Finally, the solid powder of L-CQDs was obtained by freeze drying for later use.

[0034] (2) Preparation of CNF: Hydrogen peroxide (30%) and acetic acid (≥99%) were mixed in a beaker at a volume ratio of 1:1 to obtain a peroxy-acetic acid solution. 10 g of sugarcane bagasse was placed in a conical flask and HPAA solution (V HPAA :V 水 =100:0), then add 100mM sulfuric acid solution as a catalyst, and adjust the solid-liquid ratio to 1:10 (W / V), after fully mixing, place in a constant temperature water bath, pre-treat at 80°C for 2h, after the water bath ends, cool to room temperature, use a separatory funnel to achieve solid-liquid separation, and then use deionized water to rinse the solid residue to neutrality, transfer the washed solid to an electric hot air drying oven and dry at 40°C to obtain bagasse slurry; add deionized water to the obtained bagasse slurry to adjust the concentration to 1wt%, soak for 24h, and then de-ionize the soaked slurry for 15min to prepare a 2wt% fiber suspension, and then grind the fiber suspension. During the grinding process, the method for regulating the distance between the grinding stones is as follows: when the ultrafine grinding machine is idling, the critical point where the two grinding stones initially contact is defined as the dynamic zero point. After the slurry is added, the distance between the two grinding stones is gradually adjusted from the dynamic zero point to -100μm, and then ground for 2h to obtain CNF samples, which are stored in a refrigerator for standby use;

[0035] (3) Preparation of fluorescent composite film: 5 mg of L-CQDs powder was added to 5 mL of deionized water to form a transparent and clear L-CQDs solution. The L-CQDs solution was mixed with 0.3 g of CNF (absolutely dry) and mechanically stirred at room temperature for 1 h at a speed of 600 rpm to allow the L-CQDs to be evenly dispersed in the CNF solution. The resulting mixture solution was then ultrasonically treated to remove bubbles. The L-CQDs / CNF solution obtained after ultrasonic treatment was then added to a mold for casting and precipitated at room temperature to finally obtain a fluorescent composite film.

[0036] Embodiment 3:

[0037] This embodiment provides a method for preparing a fluorescent composite film, the method comprising the following steps:

[0038] (1) Preparation of L-CQDs: 0.1 g of 3,5-diaminobenzoic acid was added to 0.1 g of alkali lignin, followed by 19 mL of deionized water and 1 mL of sulfuric acid. After mixing, the mixture was transferred to a 50 mL polytetrafluoroethylene-lined stainless steel reactor. The reactor was placed in an electric heated blast drying oven and reacted at 220 °C for 14 h. After the reaction was completed, the reaction mixture was naturally cooled to room temperature. The obtained product was then filtered with a 0.22 μm nylon microporous membrane. The supernatant was dialyzed in ultrapure water using a dialysis bag (MWCO = 1000 Da) for 4 days. During this period, the water was changed every 6 h. The dialyzed solution was evaporated using a parallel concentrator to reduce some of the water content. Finally, the L-CQDs solid powder was freeze-dried for later use.

[0039] (2) Preparation of CNF: Hydrogen peroxide (30%) and acetic acid (≥99%) were mixed in a beaker at a volume ratio of 1:1 to obtain a peroxy-acetic acid solution. 10 g of sugarcane bagasse was placed in a conical flask and HPAA solution (V HPAA :V 水 =100:0), then add 100mM sulfuric acid solution as a catalyst, and adjust the solid-liquid ratio to 1:12 (W / V), after fully mixing, place in a constant temperature water bath, pre-treat at 90°C for 3h, after the water bath ends, cool to room temperature, use a separatory funnel to achieve solid-liquid separation, and then use deionized water to rinse the solid residue to neutrality, transfer the washed solid to an electric hot air drying oven and dry at 40°C to obtain bagasse slurry; add deionized water to the obtained bagasse slurry to adjust the concentration to 2wt%, soak for 25h, and then de-ionize the soaked slurry for 20min to prepare a 3wt% fiber suspension, and then grind the fiber suspension. During the grinding process, the method for regulating the distance between the grinding stones is as follows: when the ultrafine grinding machine is idling, the critical point where the two grinding stones initially contact is defined as the dynamic zero point. After the slurry is added, the distance between the two grinding stones is gradually adjusted from the dynamic zero point to -100μm, and then ground for 2h to obtain CNF samples, which are stored in a refrigerator for standby use;

[0040] (3) Preparation of fluorescent composite film: 5 mg of L-CQDs powder was added to 5 mL of deionized water to form a transparent and clear L-CQDs solution. The L-CQDs solution was mixed with 0.3 g of CNF (absolutely dry) and mechanically stirred at room temperature for 1 h at a speed of 600 rpm to allow the L-CQDs to be evenly dispersed in the CNF solution. The resulting mixture solution was then ultrasonically treated to remove bubbles. The L-CQDs / CNF solution obtained after ultrasonic treatment was then added to a mold for casting and precipitated at room temperature to finally obtain a fluorescent composite film.

[0041] Embodiment 4:

[0042] The present embodiment provides a method for preparing a light-emitting diode, wherein the light-emitting diode is obtained by treating an LED lamp bead with the fluorescent composite film described in Example 2. The specific method is as follows: a layer of ultraviolet light-curing glue is applied to the edge of a 1W ultraviolet LED lamp bead, with a powder-to-glue mass ratio of 1:1, and then, the fluorescent composite film is taken to cover the surface of the lamp bead. At the same time, in order to realize LED film encapsulation and the application of LED in a humid environment, a layer of ultraviolet light-curing glue is applied to the surface of the fluorescent composite film, and a 365nm ultraviolet lamp is used for irradiation for 3 minutes for light curing, and the treated LED device (i.e., the light-emitting diode) can be obtained.

[0043] Test example 1:

[0044] The applicant analyzed the L-CQDs obtained from the preparation experiment:

[0045] First, the experimental raw materials 3,4-diaminobenzoic acid, 3,5-diaminobenzoic acid and sulfuric acid were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; alkali lignin was purchased from Sigma-Aldrich, a subsidiary of Merck in Germany.

[0046] Based on the method of Example 2, the product prepared by using alkali lignin and 3,4-diaminobenzoic acid is blue carbon quantum dots, recorded as BL-CQDs, and the product prepared by using alkali lignin and 3,5-diaminobenzoic acid is green carbon quantum dots, recorded as GL-CQDs;

[0047] The time-resolved photoluminescence spectra of BL-CQDs (350nm / 450nm) and GL-CQDs (410nm / 505nm) were tested at the optimal excitation wavelength and the optimal emission wavelength, and the fluorescence lifetimes of the two L-CQDs were analyzed. The average lifetimes of BL-CQDs and GL-CQDs were 6.61ns and 4.26ns, respectively, indicating that after the two L-CQDs absorbed light, BL-CQDs stayed in the excited state for a longer time and had a higher fluorescence efficiency.

[0048] Test Example 2:

[0049] The applicant analyzed the prepared CNF:

[0050] The raw materials of the experiment were sugarcane bagasse provided by a local sugar factory (Guangxi, China), and the raw materials were ground and sieved to 40-60 mesh; bleached bagasse pulp was provided by Yunnan Yunjing Forestry and Paper Co., Ltd. as a control group. Hydrogen peroxide (30%), acetic acid (99%), and sulfuric acid (98%) were all analytically pure and purchased from Aladdin Chemical Reagent Co., Ltd.

[0051] Based on Example 2, change V HPAA :V水 The ratios were 0:100, 1:1:, and 100:0, respectively; they were named BG-0, BG-50, and BG-100 samples, respectively; in addition, the CNF prepared from bleached bagasse pulp (BBK) containing trace lignin was named CNF-BBK.

[0052] First, during the HPAA pretreatment of bagasse, H 2 SO 4 The chemical compositions of bagasse pulp samples prepared with different pretreatment degrees are as follows: Figure 1 By controlling the concentration of HPAA, BG-0, BG-50 and BG-100 samples with lignin contents of 23.87%, 14.26% and 3.92% were obtained, and BG-BBK was used as a control sample (lignin content <1%).

[0053] Next, the energy consumed in the mechanical grinding of CNF was measured using a digital electrical parameter measuring instrument, and the idling power of the ultrafine grinding machine was 0.37 kW. The energy consumption of each sample was ranked as LCNF-0 (52.03 kWh / Kg) > LCNF-50 ((41.86 kWh / Kg) > LCNF-100 ((31.13 kWh / Kg) > CNF-BBK ((29.89 kWh / Kg). It can be seen that with the increase in the degree of pretreatment, the mechanical energy consumption gradually decreases. This is because a large amount of lignin is covered and cross-linked on the surface of cellulose fibers through LCC, which hinders the separation between fibers and inhibits its microfibrillation process. At the same time, it was found that the energy consumption consumed by LCNF-100 was close to that of CNF-BBK, which shows that by only changing the degree of pretreatment of bagasse, it is possible to achieve energy consumption comparable to that of CNF-BBK in the preparation of CNF while retaining a certain lignin content.

[0054] In addition, the optical properties of CNF films were analyzed. Figure 2 As shown, Figure 2 (a) is the CNF film transmittance (200-800nm), Figure 2 (b) is the haze of the CNF film sample, Figure 2 (c) is the transparency and haze value of the CNF film sample at 600nm, Figure 2(d) is a photograph of the film (0.3 g of CNF with an absolute dry weight was ultrasonically treated for 30 minutes, and then the CNF film was prepared by the casting method). The high transmittance CNF film can transmit light energy, which is of great significance as a substrate or functional component of optoelectronic devices. The transmittance of LCNF-100 film and CNF-BBK film is significantly higher than that of LCNF-0 film and LCNF-50 film. Both of them have a transmittance of more than 80% in the visible light range of 380-780nm, meeting the application requirements of LED packaging materials. Optically transparent films with haze are gaining more and more attention due to their unique properties in optoelectronics. High haze CNF films (>40%) have anti-glare properties and can meet the requirements of display use under strong sunlight.

[0055] Finally, the water barrier performance of CNF membrane was analyzed. Figure 3 Schematic diagram showing the water contact angle of cellulose films with different lignin contents. Figure 3 As shown in the figure, with the increase of lignin content, the contact angle increases from 68.7° to 97.3°, indicating that the increase of lignin content can effectively improve the water barrier properties of CNF film. This is because lignin contains a large number of aromatic groups and has lower hydrophilicity than cellulose. When there is a large amount of lignin in the sample, it can wrap the cellulose surface and reduce the free hydroxyl groups on the fiber surface, thereby reducing the mutual adsorption with water molecules. Compared with the CNF-BBK film prepared from bleached pulp, the water contact angle of LCNF-100 film increased by nearly 10°, indicating that the presence of a small amount of lignin is also very beneficial to improve the water resistance of CNF film. The water contact angle (77.6°) of the LCNF-100 film obtained in this study is higher than that of PVA (66.5°) and flexible nanopaper (45.3°), indicating that it has good water barrier properties. In summary, LCNF-100 film has great application potential in LED matrix materials.

[0056] Combining Experiment 1 and Experiment 2, LCNF-100 was selected as CNF and BL-CQDs were selected as L-CQDs as constituent raw materials. A fluorescent composite film was prepared according to step (3) of Example 3 and applied to the preparation of LEDs.

[0057] The excitation light source of the L-LED device uses a 365nm ultraviolet light-emitting diode chip, and the light-emitting layer uses the BL-CQDs / LCNF-100 fluorescent composite film with the best comprehensive performance in the above research. The BL-CQDs / LCNF-100 LED device was obtained by light-curing rapid thin film packaging technology.

[0058] The BL-CQDs / LCNF-100LED has a peak emission wavelength of 560nm in the on state, showing uniform and bright green emission (such as Figure 4(a)-(b)), this is because the UV LED chip itself emits white light, and after the BL-CQDs / LCNF-100 fluorescent composite film is combined with it, the light emitted is a mixture of the white light of the LED chip and the fluorescence of the BL-CQDs / LCNF-100 fluorescent composite film, so the wavelength is red-shifted. Through the International Commission on Illumination (CIE) 1931 color gamut space, the CIE coordinates of the BL-CQDs / LCNF-100 LED emission spectrum are calculated to be (0.39, 0.47) ( Figure 4 (c) The photometric parameters of the LED device were further measured. The luminous flux and luminous efficiency were 0.176lm and 0.616lmW respectively. -1 .

[0059] LED is usually driven by constant current. In order to test the effect of current change on BL-CQDs / LCNF-100LED, a current fluctuation test experiment was conducted on BL-CQDs / LCNF-100LED to check its chromaticity stability. Figure 5 As shown in (a), the EL intensity of the BL-CQDs / LCNF-100LED device increases with the driving current from 20mA to 120mA. When the driving current increases from 20mA to 120mA, the CIE color coordinates shift from (0.3899, 0.4666) to ((0.3948, 0.4677), with almost no change; at the same time, the luminous efficiency of the BL-CQDs / LCNF-100LED device increases from 0.616lmW to -1 Slightly decreased to 0.484lm W -1 ( Figure 5 c).

[0060] The above results show that the LED prepared by the fluorescent composite film based on BL-CQDs and LCNF-100 has good luminescence stability and can be used in the optoelectronic field.

[0061] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a fluorescent composite film, characterized in that: The method comprises the following steps: (1) Preparation of L-CQDs: 3,4-diaminobenzoic acid or 3,5-diaminobenzoic acid is added to alkaline lignin, followed by deionized water and sulfuric acid. After mixing, the mixture is transferred to a reactor, and the reactor is placed in an electric heating blast drying oven. The reaction is carried out at 180-220° C. for 10-14 h. After the reaction is completed, the reaction is naturally cooled to room temperature. The obtained product is then filtered, and the supernatant is dialyzed in ultrapure water for 2-4 days using a dialysis bag. The dialyzed solution is evaporated and freeze-dried to obtain L-CQDs solid powder for later use; (2) Preparation of CNF: Mix hydrogen peroxide and acetic acid in a beaker to obtain a peroxy-acetic acid solution, place bagasse in a conical flask, add HPAA solution, then add sulfuric acid solution, and adjust the solid-liquid ratio to 1:8-12. After sufficient mixing, place in a constant temperature water bath and pre-treat at 70-90°C for 1-3 hours. After the water bath ends, cool to room temperature, rinse the solid residue with deionized water to neutrality after solid-liquid separation, and dry the washed solid to obtain bagasse slurry; add deionized water to the obtained bagasse slurry to adjust the concentration to 1-2wt%, soak for 22-25 hours, and then decompose the soaked slurry for 10-20 minutes to prepare a 1-3wt% fiber suspension. Then, grind the fiber suspension to obtain a CNF sample; (3) Preparation of fluorescent composite film: L-CQDs powder was added to deionized water to form a transparent and clear L-CQDs solution, the L-CQDs solution was mixed with CNF, and stirred at room temperature to be evenly dispersed, and then the resulting mixture solution was ultrasonically treated. The L-CQDs / CNF solution obtained after ultrasonic treatment was added to a mold for casting and precipitated at room temperature to finally obtain a fluorescent composite film.

2. The method according to claim 1, characterized in that In the step (1), the mass ratio of alkali lignin to 3,4-diaminobenzoic acid or 3,5-diaminobenzoic acid is 1:1, the liquid ratio of deionized water added to alkali lignin is 1g:190mL; the liquid ratio of sulfuric acid added to alkali lignin is 1g:10mL.

3. The method according to claim 1, characterized in that In the step (1), the product is filtered using a 0.22 μm nylon microporous membrane, and the supernatant is dialyzed in ultrapure water using a dialysis bag for 3 days, during which the water is changed every 6 hours.

4. The method according to claim 1, characterized in that: In the step (2), the volume ratio of hydrogen peroxide to acetic acid is 1:

1.

5. The method according to claim 1, characterized in that During the grinding process in step (2), the distance between the grinding stones is regulated as follows: when the ultrafine grinding machine is idling, the critical point where the two grinding stones initially contact is defined as the dynamic zero point. After the slurry is added, the distance between the two grinding stones is gradually adjusted from the dynamic zero point to -100 μm, and then grinding is performed for 2 hours.

6. The method according to claim 1, characterized in that The solid-to-liquid ratio of the L-CQDs powder and deionized water in step (3) is 1 mg:1 mL, and the mass ratio of the L-CQDs powder to CNF is 1:

60.

7. Use of the fluorescent composite film according to claims 1-6 in the preparation of light-emitting diodes.

8. A method for preparing a light emitting diode, characterized in that: The light-emitting diode is prepared by assembling the fluorescent composite film described in any one of claims 1 to 6 as the LED light-emitting layer. The specific method is as follows: a layer of ultraviolet light-curing glue is applied to the edge of a 1W ultraviolet LED lamp bead, with a powder-to-glue mass ratio of 1:1, and then the fluorescent composite film is taken to cover the surface of the lamp bead. At the same time, in order to realize LED film encapsulation and the application of LED in a humid environment, a layer of ultraviolet light-curing glue is applied to the surface of the fluorescent composite film, and a 365nm ultraviolet lamp is used for irradiation for 3 minutes for light curing, so that the treated LED device can be obtained.